2009
DOI: 10.1007/s12263-009-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity increases NF-κB signaling in reporter mice

Abstract: The nuclear factor (NF)-kappaB is a primary regulator of inflammatory responses and may be linked to pathology associated with obesity. We investigated the progression of NF-kappaB activity during a 12-week feeding period on a high-fat diet (HFD) or a low-fat diet (LFD) using NF-kappaB luciferase reporter mice. In vivo imaging of luciferase activity showed that NF-kappaB activity was higher in the HFD mice compared with LFD-fed mice. Thorax region of HFD females displayed fourfold higher activity compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 32 publications
6
67
0
1
Order By: Relevance
“…In our study NFκB p50 was significantly increased in heart lysates of obese female rats. This finding is in agreement with others showing that a HF diet has a proinflammatory effect, increasing NFκB activity in several tissues [55][56][57][58].…”
Section: Discussionsupporting
confidence: 93%
“…In our study NFκB p50 was significantly increased in heart lysates of obese female rats. This finding is in agreement with others showing that a HF diet has a proinflammatory effect, increasing NFκB activity in several tissues [55][56][57][58].…”
Section: Discussionsupporting
confidence: 93%
“…Recent reports showed that HFD stimulate NF-κB in obese mice [28]. In our study we used non-obese NF-κB-Luc transgenic mice fed with HFD for 4, 8, and 12 weeks, and compared with mice fed on RD, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from our laboratory have reported that IL-1β-induced NF-κB activity contributes in chemoattractant urging initial phase of prostatic inflammation that might have a capability for maintaining the chronic inflammation and proliferative inflammatory atrophy (PIA) in the prostrate, which are recognized as putative precursor lesions in the development of prostrate cancer [27]. Recently it has been shown that high-fat diet (HFD) is a stimulator for NF-κB responses in diet-induced obese mice [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Class II obesity and depression are set as exclusion criteria to prevent confounding, due to the association between depression and sleep disturbance [28] and because of the effect of both depression and obesity on inflammatory markers. [29, 30] Trained study staff will complete the eligibility assessments at initial contact to participants over the phone in a one-to-one interview. During this initial contact, PSQI and illness exclusions will be assessed to ensure eligibility.…”
Section: Eligibility Requirementsmentioning
confidence: 99%